Base Isolation of Buildings with Curved Surface Sliders: Basic Design Criteria and Critical Issues - Fernando Saitta; Paolo Clemente; Giacomo Buffarini; Giovanni Bongiovanni; Antonello Salvatori; Cristian Grossi (Advances in Civil Engineering)
Curved surface sliders are being used more and more in the seismic isolation of buildings. They are preferred not only because of their lower cost with respect to elastomeric isolators but also of their technical characteristics, such as the fact that the value of the period of vibration is independent of the mass and the automatic coincidence between the gravity mass center of the superstructure and the stiffness center of the isolation system. In this paper, these features are analysed with reference to simple structures, pointing out the possibility of rotations of the superstructure and the loss of contact in some devices. Finally, the importance of the static friction is also emphasized showing the experimental seismic response of an isolation system under a low-energy earthquake. For all these reasons, the use of nonlinear analysis, revised and detailed in this paper, is advisable for the isolation system made of curved surface sliders.